105k views
3 votes
Solve. 2x − 9y = 11 ,x = -8

2 Answers

2 votes

Answer: Y= -3

Explanation:

So we have x already, and we need to solve for y.

We plug in x, 2(-8) -9y = 11

Which gives us -16 - 9y= 11

Then we subtract (-16): -9y=27

Then, we divide by -9: y= -3

So your answer is y= -3

User Matthew Plourde
by
5.5k points
5 votes

Substitute x with -8.

2(-8) - 9y = 11

-16 - 9y = 11

Now, solve for y.

-16 + 16 - 9y = 11 + 16

-9y = 27

-9y/-9 = 27/-9

y = -3

Hope This Helped! Good Luck!

User Saba Jamalian
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.